Trust in online hotel reviews across review polarity and hotel category - Banerjee, Snehasish (2020)
This paper investigates how users' perception of online hotel reviews is related to trust across review polarity and hotel category. Users' perception of both titles and descriptions of reviews was examined. Data came from a 2 (review polarity: positive and negative) x 2 (hotel category: luxury and budget) between-participants experiment. Analysis was done using the partial least squares structural equation modeling approach. Attractiveness of titles and credibility of descriptions were positively related to trust. Moreover, the relation between users' perception of reviews and their decision to trust differed significantly across review polarity and hotel category. Implications of the findings are highlighted.